Achieving A Competitive Advantage Supply Chain Management Practices and Responsiveness - Muhammad, Rosliniwati; Saad, Shatina (Information Management and Business Review, 2023)
Today’s business environment is highly competitive and globalized, characterized by shorter product life cycles and demanding customers. As a result, supply chains must be responsive to changes in the marketplace to maintain and create a competitive advantage. While previous studies have acknowledged the advantages of effective supply chain management (SCM) in gaining a competitive edge, there remains a limited understanding of the implications of adopting various SCM practices. To address this gap, this conceptual study focuses on examining the relationship between SCM practices (strategic supplier partnership, customer relationship, information sharing, and postponement) and both supply chain responsiveness and competitive advantage within the Malaysian timber industry. The study integrates the Resources Based View (RBV), Dynamic Capabilities theory, and Natural Resource-Based View (NRBV) theory.